PENGEMBANGAN BUKU DIGITAL BERBANTUAN APLIKASI SIGIL BERBASIS DISCOVERY LEARNING TERHADAP SELF EFFICACY PESERTA DIDIK - Kurniawan, Romi (Jurnal Riset Pendidikan Dasar Dan Karakter, 2022)
Development research has been conducted that produces teaching materials in the form of digital physics books aided by the application of Sigil based on discovery learning to students' self efficacy on optical devices and global warming. The study was conducted at MAN 2 Padang in class XI MIA 4 and XI MIA 6. The research method used was Research and Development and refers to the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The physics digital book was validated by 2 material expert lecturers, 2 media expert lecturers, and 1 linguist lecturer, and tested by 2 educators and 10 students for practicality, and 31 students for effectiveness. The results of the validation and trial show that digital books on optical material are said to be very valid with a value of 93.66, very practical with a value of 85.4 and very effective 85.28. While the global warming material is said to be very valid 93.66, very practical with a value of 85.46, and very effective with a value of 85.28. Based on the results of the acquisition of data shows that digital books aided by the application of Sigil based on discovery learning on the self efficacy of students are categorized as very valid, very practical, and very effective in using physics learning.